Micropropagation of Wooden Banana (Musa paradisiaca L. cv. Kayu) Through In Vitro - Maulia Sustiana; Aida Muspi'ah; Nur Indah Julisaniah (JRST (Jurnal Riset Sains dan Teknologi), 2026)
Wooden banana (Musa paradisiaca L. cv. Kayu) is a local banana variety that had unique characteristics, including a sweet taste, fragrant aroma, thicker skin, longer shelf life, and high economic value. This banana variety had a long growth period, requiring approximately 9 to 11 months to flower and bear fruit. Additionally, a single plant usually produced only one to three suckers, making wooden banana seedlings rare and difficult to obtain. To prevent its potential extinction, seedling propagation was necessary, with one possible solution being tissue culture techniques.   This study aimed to determine the optimal concentration of Benzyl Amino Purine (BAP) and the most effective culture medium for the growth of wooden banana shoots. The research employed an experimental method, testing various BAP concentrations (1 ppm, 2 ppm, 3 ppm, 4 ppm, and 5 ppm) on solid and semi-solid culture media. Data were analyzed descriptively based on the number of shoots produced under each treatment. The results showed that concentration of 3 ppm Benzyl Amino Purine (BAP) produced the highest shoot proliferation. The solid-liquid medium was the most effective culture medium, which produced an average of 4.33 shoots per explant. These findings indicate that appropriate BAP concentration and culture medium significantly enhance in vitro micropropagation of wooden banana.